Pengaruh Profitabilitas Dan Kualitas Audit Terhadap Agresivitas Pajak - Komang Dian Suastini; Nyoman Ari Surya Dharmawan (Universitas Pendidikan Ganesha, 2025)
The purpose of this study is to determine the influence of profitability variables and audit quality on tax aggressiveness both partially and simultaneously. This research is a quantitative research conducted on food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample of this study was selected using purposive sampling with several criteria. There are 23 companies that are used as a sample, so the number of research samples is 115 companies. However, there are 15 data that are outlier so that the final sample in this study is 100 samples. The data used in this study is secondary data obtained through the company's financial statements. The data analysis techniques used consisted of descriptive statistical tests, classical assumption tests, and hypothesis tests. The results of the study show that profitability have no effect on tax aggressiveness, while audit quality has a negative effect on tax aggressiveness. Simultaneously, profitability and audit quality have a significant effect on tax aggressiveness with an influence rate of 9.1%.